The Formation of Urban Traditions in Bukhara (From Ancient Times to the Years of Independence) - Hayotova Nafisa Zakirovna (Researchparks Publishing, 2023)
This article provides information about the formation and development of urban planning traditions in Bukhara. Over the centuries, many creative works were carried out in the ancient city of Bukhara during different dynasties. The city became known to the world as a center of knowledge and trade. Although the formation of urban culture in Bukhara was mainly developed from the time of the Soviet government,Many mistakes were made during the construction of the city. First of all, natural factors were not taken into account in the construction of the city, especially the direction of the wind was not taken into account in the construction of residential and social buildings. This situation made it difficult to exchange air in these buildings. Secondly, not enough attention has been paid to the greening of the city, that is, to the establishment of the